Explicación paso a paso:
[tex]P(x)=3x(6x-8)+4x(9-2x)\\P(x)=18x^2-24x+36x-8x^2\\P(x)=10x^2+12x[/tex]
[tex]Q(x)=5x^2+8(3x^2-2x)\\Q(x)=5x^2 +24x^2-16x\\Q(x)=29x^2-16x[/tex]
[tex]P(x)+Q(x)=10x^2+12x + 29x^2-16x\\P(x)+Q(x)=39x^2-4x[/tex]
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Explicación paso a paso:
[tex]P(x)=3x(6x-8)+4x(9-2x)\\P(x)=18x^2-24x+36x-8x^2\\P(x)=10x^2+12x[/tex]
[tex]Q(x)=5x^2+8(3x^2-2x)\\Q(x)=5x^2 +24x^2-16x\\Q(x)=29x^2-16x[/tex]
[tex]P(x)+Q(x)=10x^2+12x + 29x^2-16x\\P(x)+Q(x)=39x^2-4x[/tex]